Comparison of the Main Characters in the Fairy Tale Hänsel und Gretel by the Brothers Grimm in 1812 and Gunter Preuß in 2021 - Keisha Rafa Anandhita; Fauzan Adhima; Kurniasih Ratri Handayani (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2025)
This study compares the main characters Hänsel and Gretel in the fairy tale Hänsel und Gretel by Bruder Grimm (1812) and Neues von Hänsel und Gretel by Gunter Preuß (2021) using the Big Five Model. Employing a descriptive qualitative method, it analyzes words, phrases, and sentences from narratives, monologues, and dialogues depicting their traits. Findings reveal similarities in three dimensions, Offenheit für Erfahrung, Verträglichkeit/Anpassung, and Neurozitismus as survival defense mechanisms in both versions. Differences emerge in the Grimm version, emphasizing Gewissenhaftigkeit for both characters, while Preuß portrays Hänsel with heightened Neurozitismus and Gretel with Extraversion. Data increased significantly (Hänsel: 8 to 19; Gretel: 8 to 15; total 50), reflecting more complex emotional dynamics and inner conflicts in the modern adaptation, shifting from physical poverty survival to familial mental pressures. This evolution proves fairy tale characterizations adapt to contemporary real-world issues.